Learning Science in Primary Education with STEM Workshops: Analysis of Teaching Effectiveness from a Cognitive and Emotional Perspective - Mateos-Núñez, Milagros; Martínez-Borreguero, Guadalupe; Naranjo-Correa, Francisco Luis (Sustainability, 2020)
Several international institutions emphasize the need to develop a comprehensive education in STEM areas (Science, Technology, Engineering, Mathematics) to improve learning, competences and student perception of these subjects. The general objective of this study was to analyze the teaching effectiveness, from a cognitive and emotional perspective, of a STEM workshop versus an academic-expositional methodology in the science classroom in primary education. The research design was quasi-experimental with a control group, an experimental group, a pre-test and two post-tests. By means of a randomized probabilistic sampling, 256 students between 10 and 12 years old participated. Cognitive, emotional, attitudinal and gender variables were analyzed according to two teaching methodologies, an expository academic methodology for the control group and an active methodology based on the development of a practical STEM workshop for the experimental group. The results reveal that both methodologies are equally effective in short-term learning, but statistically significant differences are found in long-term learning, in favor of STEM workshops. Likewise, the STEM workshop mainly generates positive emotions and attitudes in the students compared to the transmission-reception methodology applied with the control group.